PROFESSIONAL EXAMINATIONS A Departments for Students of Accounting. - Chamberlain, Henry T. (The Accounting Review, 1945)
The article presents information on the professional accounting examination. The following problems are the first half of the May 1943, Certified Public Accountants examination in accounting practice prepared by the Board of Examiners of the American Institute of Accountants. The examinee was given four and a half hours to solve problem 1 and either problem 2 or problem 3. The problems were weighted as follows: problem 1, thirty points; problems 2 and 3, twenty points. A suggested time schedule was given: ninety minutes for problem 1, sixty minutes for problem 2 and ninety minutes for problem 3. Problem 1 was concerned with the preparation of a consolidated balance-sheet of H Co. and subsidiaries, A Co. and B Co., as at December 31, 1944. Problem 2 was concerned with the determination of the net income (before federal taxes on income) of Ace Co. Inc. for 1944 in conformity with generally accepted accounting principles and prepare a reconciliation of such net income and normal tax net income. Problem 3 was again concerned with the preparation of the balance sheet working papers for each of the following funds of Morton City as of February 28, 1944.